Therapy and prophylaxis of brain metastases - Kienast, Yvonne; Winkler, Frank (Expert review of anticancer therapy, 2010)
Metastases of various tumors to the brain account for the majority of brain cancers, and are associated with a poor prognosis. The most common primary sites are lung, breast, skin, kidney and colon; 10-40% of cancer patients develop brain metastases during the course of the disease. The incidence of brain metastasis appears to be rising; reasons may include better therapies for the systemic disease with longer survival of cancer patients but lower efficiency against brain metastases. In this article, we will discuss the conventional treatment with surgery, radiosurgery, radiotherapy and chemotherapy, but also new directions in the management of solid brain metastases. While general therapeutic nihilism should be avoided, it is important to recognize that the number of brain metastases, the extent of the systemic disease and also the tumor type have to be taken into account when choosing individual treatment regimens. Finally, special emphasis will be put on established and future approaches to prevent the disease. We thus aim to provide a framework for treating patients with different presentations of brain metastases, and to highlight important avenues for research.